Jenis – jenis tumbuhan paku (Pteridofita) dari Hutan Universitas Riau, Provinsi Riaudan Pola Pita DNA berdasarkan Penanda DNA M13Primer - Sofiyanti, Nery; Isda, Mayta Novaliza (Biospecies, 2019)
University of Riau Forest, Riau Province is one of distribution area of ferns (Pteridophytes). This study aimed to identify fern species at University of Riau Forest and examined the DNA band pattern based on M13 DNA marker. Samples were collected from the field using exploration method and were then identified. DNA isolation was carried out using DNAeasy Plant Mini Kit (Qiagen), and amplified based on PCR method using DreamTaq Green PCR Master Mix (2X) (Thermo Scientific) with M13 DNA Marker. The inventorisation result showed a total of 26 fern species belong to 8 families were identified in this study. The electrophoresis result of PCR product gave the variaous DNA band pattern ranged from 200 to 2000 bp. DNA band pattern using M13 primer can be used to support the taxonomical data of fern taxa